Recent applications of albumin as a green and versatile catalyst in organic synthesis - Borucki, Estefanía Lorena (2025)
Today, biocatalytic methodologies are well established as useful tools in green organicsynthesis, since biocatalysts are mild, sustainable, and environmentally friendly catalystswhich provide selectivity to the reactions they catalyse. Albumin, the most abundantprotein of mammalian blood, is a versatile and mild biocatalyst in vitro. The aim ofthis review is to provide a perspective on the synthetic applications of albumin over thelast decade. These cover transformations with a diverse chemical basis, such as additions,eliminations, and oxidations, including formation of carbon–carbon and carbon–heteroatombonds. Albumin can also be applied in tandem and multicomponent reactions and offers amild alternative for the synthesis of different heterocyclic cores. In addition to its syntheticpossibilities, the remarkable reusability of this protein offers interesting potential from abiotechnological point of view.